ANALISIS HUKUM TERHADAP TABANNI (PENGANGKATAN ANAK) MENURUT FIKIH ISLAM DAN UNDANG-UNDANG NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK - MITRA SUPRAYUDI (PREMISE LAW JURNAL, 2014)
ABSTRACT Child adoption (tabanni) in Indonesian community has several purposes which among other things to continue descendants if a marriage fails to give offspring. The problem of tabanni (child adoption) practices by the community in general is by removing the status or relationship between the adopted child and his/her biological parents or deliberately, the adopted parents do not tell their adopted child that he/she is not their biological child. Child adoption which removes the blood relationship (nasab) is not allowed in Islamic Law while what is allowed is the child adoption in sense of taking care of the child without removing the child’s blood relationship with his/her biological parents. According to Law No. 23/2002 on Child Protection, child adoption is the transfer of the rights of a child from his/her biological parents to his/her adopted parents for the best of the child adopted. The procedure is that child adoption can be done in Religious Court or State Court (for non-Muslim). What is trasferred is only the right of guarduanship of the child. In relation to inheritance, the child adopted based on court decision has the right to receive inheritance from his/her adopted parents under the wajibah will. The protection for the child adopted based on the court decision is that his/her legal guardianship and the distribution of inherited property from his/her adopted perents are guaranteed. Keywords: Legal Analysis, Child Adoption